Dual-band and broadband tunable absorber based on Weyl semimetals. (1st August 2022) - Dai, Linlin; Zhang, Yuping; Zhang, Huiyun; Qi, Limei; Uqaili, Junaid Ahmed
Abstract: The density of the electric and the magnetic fields reveal the physical mechanisms of the absorption phenomenon. This paper presents perfect dual-band and broadband absorbers formed by Weyl semimetals (WSMs) and dielectric layers above the metallic ground plane. The tunability of absorption frequencies is achieved by changing the chemical potential of WSMs. The influence of structure parameters on dual-band absorption is also investigated. The dual-band absorbers shows absorptivity over 99% and are insensitive to the polarization angle of electromagnetic waves. The broadband absorbers show absorptivity over 80% in the wideband range of 2.49–4.96 THz. This proposed absorber has significant potential in terahertz detection, radar stealth, and biological monitoring.